Subsidiary Autonomy: The Case of Multinational Subsidiaries in Malaysia - Edwards, Ron; Ahmad, Adlina; Moss, Simon (Journal of International Business Studies, 2002)
This paper argues that the nature and extent of the benefits that FDI confers on host economies depends in part on the degree of autonomy enjoyed by subsidiary management. Survey evidence of multinational subsidiaries in Malaysia indicates that the autonomy conferred on local management is limited. Even where subsidiary management categorise their organisations as “decentralised”, their autonomy is limited to local operational matters. In general, the more integrated the subsidiaries in the global activities of the parent, the less their autonomy, which implies limits to their contribution to the Malaysian economy.